Joint design of RFID reader and tag anti-collision algorithms: a cross-layer approach - Gameiro, Atílio (2015)
This paper investigates the potential interactions between reader and tag anti-collision algorithms of passive RFID (radio frequency identification) systems. Conventionally, reader and tag anti-collision algorithms are designed by assuming that they are independent from each other. In practice, however, readers and tags usually operate in the same frequency band. Therefore, contention between their transmissions can also potentially arise. Furthermore, reader anti-collision policies directly influence the way in which tags are activated, and thus also the way in which they collide when responding to reader’s requests. In view of this and considering the growing numbers of readers and tags, independence of both schemes can not longer be considered as a realistic assumption. This paper partially fills this gap by proposing a new cross-layer framework for the joint evaluation and optimization of reader and tag anticollision algorithms. Furthermore, the paper proposes a new approach, based on a Markov model, which allows capacity and stability analysis of asymmetrical RFID systems (i.e., when readers and tags experience different channel and queuing states). The model captures the dynamics of tag activation and tag detection processes of RFID. It also represents a first step towards a joint design of physical (PHY) and medium access control layers (MAC) of RFID. The results indicate that the proposed approach provides benefits in terms of stability and capacity over conventional solutions even when readers and tags operate in different channels. The results also provide useful guidelines towards the cross-layer design of future RFID platforms.